2015
DOI: 10.1186/s11671-015-0757-y
|View full text |Cite
|
Sign up to set email alerts
|

The impact of thickness and thermal annealing on refractive index for aluminum oxide thin films deposited by atomic layer deposition

Abstract: The aluminum oxide (Al2O3) thin films with various thicknesses under 50 nm were deposited by atomic layer deposition (ALD) on silicon substrate. The surface topography investigated by atomic force microscopy (AFM) revealed that the samples were smooth and crack-free. The ellipsometric spectra of Al2O3 thin films were measured and analyzed before and after annealing in nitrogen condition in the wavelength range from 250 to 1,000 nm, respectively. The refractive index of Al2O3 thin films was described by Cauchy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(39 citation statements)
references
References 32 publications
6
33
0
Order By: Relevance
“…It was reported that the refractive index is closely related to the density of materials, being lower at lower density. Consequently, the increase in the refractive index is caused by the stress release and densification during the annealing process [38, 39]. Furthermore, for the 20 nm La 2 O 3 film, an abrupt increase in the refractive index could be observed when the annealing temperature increased from 400 to 600 °C, indicating an aggressive enhancement in the packing density upon crystallization.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that the refractive index is closely related to the density of materials, being lower at lower density. Consequently, the increase in the refractive index is caused by the stress release and densification during the annealing process [38, 39]. Furthermore, for the 20 nm La 2 O 3 film, an abrupt increase in the refractive index could be observed when the annealing temperature increased from 400 to 600 °C, indicating an aggressive enhancement in the packing density upon crystallization.…”
Section: Resultsmentioning
confidence: 99%
“…AZO thin films were deposited on p-type Si (100) by alternating diethylzinc (Zn(CH 2 CH 3 ) 2 , DEZ; Al(CH 3 ) 3 , TMA) and deionized water (H 2 O) in an ALD reactor (Picosun) at 190 °C. A typical ALD cycle for AZO consisted of 14 single cycles ZnO and 1 single cycle Al-O, while the single cycle of ZnO or Al-O consisted of 0.1 s DEZ or TMA pulse, 5 s N 2 purge, 0.1 s H 2 O pulse, and 5 s N 2 purge according to our previous reports [ 22 24 ]. The mechanism of ZnO ALD is the chemical vapor deposition reaction.…”
Section: Methodsmentioning
confidence: 99%
“…Establishing a precise value of the refractive index for the thin films is challenging, as it depends on the thickness and the growth conditions. Furthermore, some materials exhibit birefringence in the bulk form, whereas the thin films behave as isotropic materials [ 28 , 29 , 30 ].…”
Section: Theorymentioning
confidence: 99%